Respuestas

¡La mejor respuesta!
2012-05-01T06:33:23+02:00

Por propiedad de módulo:

 

\begin{gathered} \left| {2x - 3} \right| \leqslant 1 - 4x \hfill \\ \Leftrightarrow 4x - 1 \leqslant 2x - 3 \leqslant 1 - 4x \hfill \\ \Leftrightarrow 4x + 2 \leqslant 2x \leqslant 4 - 4x \hfill \\ \Leftrightarrow 2x + 1 \leqslant x \leqslant 2 - 2x \hfill \\ \end{gathered}

 

\begin{gathered} \Rightarrow 2x + 1 \leqslant x \wedge x \leqslant 2 - 2x \hfill \\ \Rightarrow x \leqslant - 1 \wedge x \leqslant \frac{2} {3} \hfill \\ S\left] { - \infty , - 1} \right] \hfill \\ \end{gathered}

 

Saludos!